Macroeconomic Factors and Islamic Stock Volatility: Evidence from Indonesia - Widyadhana, Rafi; Ryandono, Muhammad Nafik Hadi (Universitas Airlangga, 2025)
This study aims to analyze the influence of macroeconomic variables, namely gold prices, exchange rates, and inflation, on the volatility of Islamic stocks in Indonesia during the period 2013-2023. The research approach uses multiple linear regression method with quarterly data to identify the relationship between these variables on the volatility of Islamic stocks represented by the Jakarta Islamic Index (JII). The results show that gold prices and exchange rates have a positive significant influence on the volatility of Islamic stocks, while inflation shows a complex relationship pattern, depending on specific market conditions. The findings provide important insights for investors and regulators on the dynamics of the Islamic stock market in Indonesia. For investors, this research can help design more effective investment strategies, while for regulators, this research provides guidance for managing the stability of the Islamic capital market. This research is expected to serve as a reference for the development of a sustainable Islamic capital market that is responsive to macroeconomic changes.